A lithium battery positive electrode material and preparation method thereof

By adopting the gel combustion method combined with LiNixCoyMnzO2·aAl2O3·bSiO2 positive electrode material and silicate emulsion treatment, the problems of high cost and poor electrochemical stability of the positive electrode material of lithium-ion batteries are solved, and lithium-ion with high electrical performance and long cycle performance are achieved Preparation of battery positive electrode material.

CN114695872BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210227056.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-08
Publication Date
2025-01-10
Estimated Expiration
2042-03-08

AI Technical Summary

Technical Problem

The cost of existing lithium-ion battery cathode materials is high, especially due to the limited reserves of cobalt, the production cost increases, and the existing preparation methods have problems such as poor electrochemical stability, uneven particle distribution, irregular crystal shape and environmental pollution. Influences electrical performance.

Method used

The lithium battery positive electrode material with the chemical formula of LiNixCoyMnzO2·aAl2O3·bSiO2 was prepared by a gel combustion method combining silicate emulsion treatment and urea additives. Nanosilicic acid particles were used as crystal nuclei to form a crystal gel, and then perform a single and secondary sintering treatment, control particle size and morphology, and improve material strength and circulation performance.

Benefits of technology

Under low cobalt content, high first-time discharge specific capacity and first-time Coulomb efficiency are achieved, ensuring the long cycle performance and electrical properties of the material, reducing production costs, and avoiding the easy collapse of the material and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114695872B_ABST
    Figure CN114695872B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium battery positive electrode material and a preparation method thereof. The general chemical formula of the lithium battery positive electrode material is LiNi x Co y Mn z O2·aAl2O3·bSiO2, wherein x+y+z=1, 0.80≤x≤0.95, 0≤y≤0.2, 0≤z≤0.2, 0≤a≤0.1, 0<b≤0.1. The first coulomb efficiency of the battery made of the lithium battery positive electrode material can reach 93.3% or more, with high first coulomb efficiency and excellent electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery positive electrode materials, and in particular relates to a lithium battery positive electrode material and a preparation method thereof. Background Art

[0002] With the vigorous development of new energy vehicles, the lithium-ion battery industry has entered a stage of rapid development. The key materials that affect the performance of lithium-ion batteries are mainly positive electrode materials, negative electrode materials, electrolytes, etc. Among them, positive electrode materials are currently the main factor limiting battery performance, and are also the main factor accounting for the high cost of lithium-ion batteries, nearly 40%.

[0003] Positive electrode materials are the most critical raw materials for lithium-ion batteries and the main factors affecting the performance of lithium batteries. Currently, the commercial positive electrode materials mainly include lithium cobalt oxide, lithium manganese oxide, ternary materials and lithium iron phosphate. Among them, ternary materials have more prominent advantages in terms of cost and comprehensive performance, and have gradually become the mainstream products of positive electrode materials. Ternary materials mainly include lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese oxide materials. Among them, cobalt plays an important role in stabilizing the structure of ternary positive electrode materials. However, due to the limited reserves of metal cobalt in the world and its high price, the raw material cost and application cost of positive electrode materials for lithium-ion batteries are greatly increased. Therefore, in order to control production costs, battery manufacturers will reduce the proportion of cobalt content in ternary materials, but in general, the crystal structure is prone to collapse after reducing the cobalt content, which in turn affects the reversibility of lithium ion deintercalation during charging and discharging, resulting in extremely low first coulomb efficiency and poor electrical performance.

[0004] At the same time, the synthesis methods of ternary materials mainly include: solid phase method, coprecipitation method, solution-gel method. The solid phase method has a simple process and low cost, but poor electrochemical stability, uneven particle distribution, and irregular crystal morphology; the coprecipitation method is relatively simple and is the current mainstream process. Its main technical route for synthesis is to obtain a precursor by coprecipitation, and then to obtain the final product by heat treatment, but there are many processes, and the coprecipitation wastewater pollutes the environment. The material particles are spherical and the compaction density is not high; the existing solution-gel method mostly uses citric acid and ammonia water, the process is complicated, inconvenient to operate, and the product has a large number of micropores. During the drying process, many gases and organic matter will escape, and shrinkage will occur, making the morphology and size inconsistent. In addition, when the existing sol-gel method is used to prepare low-cobalt and cobalt-free positive electrode materials, the pore size of the porous structure obtained is uneven, and during the drying and sintering process, it is easy to shrink and collapse, etc., which affects the crystal structure and electrical properties of low-cobalt or even cobalt-free positive electrode materials. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium battery positive electrode material and a preparation method thereof, wherein the lithium battery positive electrode material has good electrical properties.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] A lithium battery positive electrode material, the general chemical formula of the lithium battery positive electrode material is LiNi x Co y Mn z O 2 ·aAl 2 O 3 bSiO 2 , where x+y+z=1, 0.80≤x≤0.95, 0≤y≤0.2, 0≤z≤0.2, 0≤a≤0.1, 0<b≤0.1.

[0008] Preferably, the lithium battery positive electrode material is composed of single-crystal-like agglomerates, and the D50 of the agglomerates is 1.0-5.0 μm.

[0009] Preferably, the quasi-single crystal is in the form of a sheet or a block, and the D50 of the quasi-single crystal is 0.1-1.5 μm.

[0010] Another object of the present invention is to provide a method for preparing the above-mentioned lithium battery positive electrode material:

[0011] A method for preparing the positive electrode material of a lithium battery as described above comprises the following steps:

[0012] (1) preparing a silicic acid emulsion and adjusting the pH to 2-3 to obtain liquid A;

[0013] (2) adding lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate to liquid A to obtain liquid B, wherein the amounts of lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate added are in an element molar ratio of Li:Ni:Co:Mn:Al:Si=1:x:y:z:2a:b;

[0014] (3) adding urea to liquid B to obtain liquid C;

[0015] (4) Liquid C is evaporated to dryness to obtain a gel, and the gel is sintered to obtain a positive electrode material for a lithium battery.

[0016] Preferably, the silicic acid emulsion prepared in step (1) is SiO 2 The concentration is 0.01-0.1 mol / L, and the amount of urea added in step (3) is 3-5 times the molar amount of nitrate in liquid B.

[0017] Preferably, the evaporation temperature in step (4) is 80-90°C.

[0018] Preferably, the sintering process in step (4) includes primary sintering, briquetting and secondary sintering.

[0019] Preferably, the primary sintering process in step (4) comprises heating the gel at a heating rate of 5-10°C / min until the gel burns, and after the combustion is completed, performing a constant temperature treatment at a temperature of 600-800°C for a time of 4-6h.

[0020] Preferably, the secondary sintering process is carried out at a constant temperature for 12-24 hours, and the constant temperature is 900-1100°C.

[0021] Preferably, the pressure of the briquetting process is 5-10 MPa, and the pressing time is 1-2 min.

[0022] A lithium battery comprises the lithium battery positive electrode material as described above.

[0023] The beneficial effects of the present invention are:

[0024] (1) The lithium battery positive electrode material of the present invention has a low cobalt content, and after the battery is manufactured, its first discharge specific capacity can reach 266 mAh / g or more, and the first coulomb efficiency can reach 93.3% or more. The battery's 300th discharge specific capacity is still 243 mAh / g or more, and the battery's capacity retention rate after the 300th discharge can reach 91.35% or more, with a high first coulomb efficiency and excellent electrical properties;

[0025] (2) The preparation method of the positive electrode material of a lithium battery of the present invention comprises the following steps: preparing a silica emulsion, using a hydrothermal evaporation method to make various metal ions and urea form a crystalline gel with nano silica particles as crystal nuclei, and then sintering the gel once under specific parameters to make the nitrate in the gel react with the urea, and then briquetting the product of the primary sintering, and finally sintering twice under specific parameters to obtain a positive electrode material of a lithium battery with uniform morphology and size. By using nano silica as the crystal nucleus, the primary particles of the material, i.e., the single crystal particles, can be made to grow uniformly during the primary sintering. The material is large, so as not to form nano-scale particles that are too small (nano-scale particles are too small and are very easy to agglomerate, and special crushing and screening treatments are required in the later stage). No special crushing and screening treatments are required. At the same time, as the temperature rises, silicic acid dehydrates to form silicon dioxide first, and in the secondary sintering stage, it forms silicate crystals with metal ions, which can further improve the strength of the material and make the material less likely to break and collapse when used as a positive electrode material, thereby improving the material's cycle performance and solving the problem that the material is easy to collapse and affect the material's cycle performance.

[0026] (3) The preparation method of the positive electrode material of the lithium battery of the present invention adopts the gel combustion method to prepare the positive electrode material. The combustion can reduce the particle size of the primary particles, so as not to produce large granular materials (when the particles are agglomerated into large lumps as positive electrode materials, they have a low specific surface area, which is not conducive to the infiltration of the electrolyte, and the specific capacity and cycle performance of the material are not ideal). By combining the crystallization of nano-silicic acid crystal nuclei with the combustion method, the particle size of the primary particles of the material is jointly controlled, thereby ensuring that the positive electrode material has a high specific surface area, thereby improving the specific capacity and cycle performance of the positive electrode material;

[0027] (4) The method for preparing the positive electrode material for a lithium battery of the present invention can improve the tap density of the material by further briquetting the combustion material, thereby improving the specific capacity of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the lithium battery positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments.

[0030] Embodiment 1:

[0031] A lithium battery positive electrode material, the general chemical formula of which is LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.1SiO 2 ;like Figure 1 As shown, its morphology is uniform single crystal-like agglomerates, and the D50 of the agglomerates is 3.5 μm; the single crystal-like morphology is block-like, and its D50 is 0.6 μm.

[0032] The method for preparing the above-mentioned lithium battery positive electrode material comprises the following steps:

[0033] (1) Preparation concentration (SiO 2 0.01 mol / L silicate emulsion, and adding nitric acid to adjust the pH to 2 to obtain liquid A;

[0034] (2) adding lithium nitrate, nickel nitrate, cobalt nitrate and manganese nitrate to liquid A according to the element molar ratio of Li:Ni:Co:Mn:Si=1:0.8:0.1:0.1:0.1, and after they are completely dissolved, obtaining liquid B;

[0035] (3) adding 3 times the molar amount of nitrate ion of urea to liquid B to obtain liquid C;

[0036] (4) evaporating liquid C to dryness at 80° C. to obtain a gel;

[0037] (5) In an air atmosphere, heating the gel at a rate of 5°C / min until the gel burns;

[0038] (6) After the combustion is completed, the temperature is kept constant at 600°C for 6 hours to obtain the combustion material;

[0039] (7) Collect the combustion materials into a sagger and press them into blocks at a pressure of 10 MPa for 1 min;

[0040] (8) The pressed sagger is placed in a roller kiln and kept at a constant temperature of 900° C. for 12 h under an oxygen atmosphere to obtain a positive electrode material for a lithium battery.

[0041] A lithium battery comprises the lithium battery positive electrode material as described above.

[0042] Embodiment 2:

[0043] A lithium battery positive electrode material, the general chemical formula of which is LiNi 0.85 Co 0.05 Mn 0.1 O 2 0.05Al 2 O 3 0.05SiO 2 ; Its morphology is a single crystal-like agglomerate, and the D50 of the agglomerate is 4.3μm; the single crystal-like morphology is block-like, and its D50 is 1.3μm.

[0044] The method for preparing the above-mentioned lithium battery positive electrode material comprises the following steps:

[0045] (1) Preparation concentration (SiO 2 0.05 mol / L silicate emulsion, and adding nitric acid to adjust the pH to 3 to obtain liquid A;

[0046] (2) adding lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate to liquid A according to the element molar ratio of Li:Ni:Co:Mn:Al:Si=1:0.85:0.05:0.1:0.1:0.05, and after they are completely dissolved, obtaining liquid B;

[0047] (3) adding 4 times the molar amount of nitrate ion of urea to liquid B to obtain liquid C;

[0048] (4) evaporating liquid C to dryness at 90° C. to obtain a gel;

[0049] (5) In an oxygen atmosphere, heating the gel at a rate of 10° C. / min until the gel burns;

[0050] (6) After the combustion is completed, the temperature is kept constant at 700°C for 5 hours to obtain the combustion material;

[0051] (7) Collect the combustion materials into a sagger and press them into blocks at a pressure of 8 MPa for 2 min;

[0052] (8) The pressed sagger is placed in a roller kiln and kept at a constant temperature of 1000° C. for 18 h under an oxygen atmosphere to obtain a positive electrode material for a lithium battery.

[0053] A lithium battery comprises the lithium battery positive electrode material as described above.

[0054] Embodiment 3:

[0055] A lithium battery positive electrode material, the general chemical formula of which is LiNi 0.95 Co 0.05 O 2 0.1Al 2 O 3 0.1SiO 2 ; Its morphology is a single crystal-like agglomerate, and the D50 of the agglomerate is 3.8μm; the single crystal-like morphology is lamellar, and its D50 is 1.0μm.

[0056] The method for preparing the above-mentioned lithium battery positive electrode material comprises the following steps:

[0057] (1) Preparation concentration (SiO 2 0.01 mol / L silicate emulsion, and adding nitric acid to adjust the pH to 2.5 to obtain liquid A;

[0058] (2) adding lithium nitrate, nickel nitrate, cobalt nitrate and aluminum nitrate to liquid A according to the element molar ratio of Li:Ni:Co:Al:Si=1:0.95:0.05:0.2:0.1, and after they are completely dissolved, obtaining liquid B;

[0059] (3) adding 5 times the molar amount of nitrate ion of urea to liquid B to obtain liquid C;

[0060] (4) evaporating liquid C at 85° C. to obtain a gel;

[0061] (5) In an air atmosphere, the gel is heated at a rate of 7° C. / min until the gel burns;

[0062] (6) After the combustion is completed, the temperature is kept constant at 800°C for 4 hours to obtain the combustion material;

[0063] (7) Collect the combustion materials into a sagger and press them into blocks at a pressure of 5 MPa for 1.5 min;

[0064] (8) The pressed sagger is placed in a roller kiln and kept at a constant temperature of 1100° C. for 12 h under an oxygen atmosphere to obtain a positive electrode material for a lithium battery.

[0065] A lithium battery comprises the lithium battery positive electrode material as described above.

[0066] Comparative Example 1:

[0067] A method for preparing a positive electrode material for a lithium battery comprises the following steps:

[0068] (1) adding lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate to pure water according to the element molar ratio of Li:Ni:Co:Mn=1:0.8:0.1:0.1, and obtaining liquid B after they are completely dissolved;

[0069] (2) adding 3 times the molar amount of nitrate ion of urea to liquid B to obtain liquid C;

[0070] (3) evaporating liquid C to dryness at 80° C. to obtain a gel;

[0071] (4) In an air atmosphere, heating the gel at a rate of 5°C / min until the gel burns;

[0072] (5) After the combustion is completed, the temperature is kept constant at 600°C for 6 hours to obtain the combustion material;

[0073] (6) The combustion material is placed in an oxygen atmosphere and kept at a constant temperature of 900° C. for 12 hours to obtain a positive electrode material for a lithium battery.

[0074] A lithium battery comprises the lithium battery positive electrode material as described above.

[0075] Comparative Example 2:

[0076] A method for preparing a positive electrode material for a lithium battery comprises the following steps:

[0077] (1) adding lithium acetate, nickel acetate, cobalt acetate, manganese acetate and aluminum acetate to pure water according to the element molar ratio of Li:Ni:Co:Mn:Al=1:0.85:0.05:0.1:0.1, and after they are completely dissolved, obtaining liquid B;

[0078] (2) Add a theoretical amount of citric acid to Liquid B, maintain the temperature at 80°C, and react for 30 minutes;

[0079] (3) After the reaction was completed, ammonia water was added to adjust the pH to 9.0;

[0080] (4) evaporating to dryness at 85°C to obtain a gel;

[0081] (5) The gel is placed in an oxygen atmosphere and kept at a constant temperature of 900° C. for 18 hours to obtain a positive electrode material for a lithium battery.

[0082] A lithium battery comprises the lithium battery positive electrode material as described above.

[0083] Test example:

[0084] The positive electrode materials of lithium batteries prepared in Examples 1-3 and Comparative Examples 1-2 were tested using a laser particle size analyzer and a tap density analyzer, and a CR2025 button battery was prepared using a lithium sheet as a reference electrode according to the positive electrode material: acetylene black: PVDF = 85:10:5. The charge and discharge performance of the button battery was tested at a voltage window of 3.0-4.3V and a current density of 1C. The test results are shown in Table 1:

[0085] Table 1: Battery performance test results

[0086]

[0087]

[0088] As shown in Table 1, the tap density of the lithium battery positive electrode material of the present invention is 2.06-2.22 g / cm 3 The first discharge specific capacity of the button battery made of the lithium battery positive electrode material of the present invention can reach 266mAh / g or more, and can reach a maximum of 284mAh / g; the first coulomb efficiency of the button battery made of the lithium battery positive electrode material of the present invention can reach 93.3% or more, and can reach a maximum of 95.6%; the 300th discharge specific capacity of the button battery made of the lithium battery positive electrode material of the present invention is still at 243mAh / g or more, and can reach a maximum of 261mAh / g; the capacity retention rate of the button battery made of the lithium battery positive electrode material of the present invention after the 300th discharge can reach 91.35% or more, and can reach a maximum of 92.42%.

[0089] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A positive electrode material for a lithium battery, characterized in that: The general chemical formula of the lithium battery positive electrode material is LiNi x Co y Mn z O2·aAl2O3·bSiO2, where x+y+z=1, 0.80≤x≤0.95, 0≤y≤0.2, 0≤z≤0.2, 0≤a≤0.1, 0<b≤0.1; The method for preparing the positive electrode material of a lithium battery comprises the following steps: (1) preparing a silicic acid emulsion and adjusting the pH to 2-3 to obtain liquid A; (2) adding lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate to liquid A to obtain liquid B, wherein the amounts of lithium nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate added are in an element molar ratio of Li:Ni:Co:Mn:Al:Si=1:x:y:z:2a:b; (3) adding urea to liquid B to obtain liquid C; (4) evaporating the liquid C to obtain a gel, and sintering the gel to obtain a positive electrode material for a lithium battery; The sintering process in step (4) includes primary sintering, briquetting and secondary sintering; The primary sintering process of step (4) comprises heating the gel at a heating rate of 5-10°C / min until the gel burns, and after the burning is completed, performing a constant temperature treatment at a temperature of 600-800°C for a time of 4-6h; The secondary sintering process is to treat at a constant temperature for 12-24 hours, and the constant temperature is 900-1100°C; The pressure of the briquetting process is 5-10 MPa, and the pressing time is 1-2 min.

2. A lithium battery positive electrode material according to claim 1, characterized in that: The lithium battery positive electrode material is composed of single crystal-like agglomerates, and the D50 of the agglomerates is 1.0-5.0 μm.

3. A lithium battery positive electrode material according to claim 2, characterized in that: The quasi-single crystal is in the form of a sheet or a block, and the D50 of the quasi-single crystal is 0.1-1.5 μm.

4. A lithium battery positive electrode material according to claim 1, characterized in that: The silicate emulsion prepared in step (1) has a concentration of 0.01-0.1 mol / L in terms of SiO2, and the amount of urea added in step (3) is 3-5 times the molar amount of nitrate in liquid B.

5. A lithium battery, characterized in that: The lithium battery positive electrode material comprises any one of claims 1 to 3.

Citation Information

Patent Citations

  • High-nickel lithium ion battery positive electrode material, preparation method thereof and lithium ion battery

    CN108987728A

  • Lithium-rich manganese-based positive electrode material with double-oxide composite coating layer and preparation method of lithium-rich manganese-based positive electrode material

    CN112310351A